2014
DOI: 10.1152/ajpheart.00553.2013
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency speckle tracking echocardiography in the assessment of left ventricular function and remodeling after murine myocardial infarction

Abstract: AM. High-frequency speckle tracking echocardiography in the assessment of left ventricular function and remodeling after murine myocardial infarction. Am J Physiol Heart Circ Physiol 306: H1371-H1383, 2014. First published February 15, 2014 doi:10.1152/ajpheart.00553.2013.-The objectives of this study were to assess the feasibility and accuracy of high-frequency speckle tracking echocardiography (STE) in a murine model of myocardial infarction (MI). STE is used clinically to quantify global and regional cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
96
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 36 publications
6
96
2
1
Order By: Relevance
“…This can be addressed with the use of the recently developed high-frequency echocardiographic systems, which represent a new platform for ultrasound-based assessment in humans with high temporal and spatial resolutions. 52 It has been recently suggested that blood motion inside the LV is characterized by diastolic vortex formation ( Figure 6B and 6C) that accompanies the redirection of jet flow toward the LV outflow tract and has a crucial role in fluid dynamics and mechanical efficiency of LV contraction. 53 LV vortex formation is closely related to the sequence of LVT and untwist, thus, warranting future studies that focus on these relationships in health and disease.…”
Section: Summary and Future Directionsmentioning
confidence: 93%
“…This can be addressed with the use of the recently developed high-frequency echocardiographic systems, which represent a new platform for ultrasound-based assessment in humans with high temporal and spatial resolutions. 52 It has been recently suggested that blood motion inside the LV is characterized by diastolic vortex formation ( Figure 6B and 6C) that accompanies the redirection of jet flow toward the LV outflow tract and has a crucial role in fluid dynamics and mechanical efficiency of LV contraction. 53 LV vortex formation is closely related to the sequence of LVT and untwist, thus, warranting future studies that focus on these relationships in health and disease.…”
Section: Summary and Future Directionsmentioning
confidence: 93%
“…Nevertheless, echocardiography in the present study was only performed with a short-axis view. A parasternal long-axis view with measurements of the area and volume change over the entire LV following MI would further enable the quantitative assessment and interpretation of regional and global cardiac function and elasticity in the remodeling murine hearts [45]. Putative mechanisms involved in FGF2/IL-10 coacervate mediated ischemic heart repair have been summarized with a schematic depiction in Supplemental Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…Strain is an early and sensitive indicator of LV global and regional systolic dysfunction, [10, 23, 24] and one goal of this study was to assess whether prior studies overlooked early indicators of loss of function in the Rad −/− heart. The Rad −/− heart exhibits increased fibrosis [2, 3, 8] yet improved EF.…”
Section: Discussionmentioning
confidence: 99%